Evaluation of microclimatic conditions during the teaching process in selected school premises. Slovak case study. (15th January 2022) - Tureková, Ivana; Marková, Iveta; Sventeková, Eva; Harangózo, Jozef
Abstract: The paper focuses on the monitoring of selected factors of the working environment in the university environment. The purpose of this study was to measure the concentration of CO2 (ppm) and to determine the proportion of dust particles (μg.m −3 ) which were compared with the recommended threshold limit values of harmful factors in the indoor environment. The measurements were performed in the classroom of the University of Constantine the Philosopher in Nitra with handheld devices PC220 and Testo 315. All measurements were carried out during the actual teaching process. The chosen variables were the occupancy of classrooms by students, time and weather conditions. Results of the measurements confirm compliance with the temperature and humidity limits in the classroom. The concentration of CO2 (ppm) with time and number of students in the classroom increased significantly and exceeded the recommended value of 1000 ppm (reached 4340 ppm). A 15-min break was considered the minimum time to ventilate the classroom and reduce the CO2 concentration. During one of the afternoon measurements, the concentration of CO2 was reduced to only 1400 ppm after 15 min of ventilation. Activities carried out during teaching process had only an insignificant effect on CO2 values. Highlights: Pleace's measurment on indoor of classroom. Temperature and humidity values in the classroom met the requirements of the legislative limits. CO2 concentration (ppm) increased with time and learners and exceeded the recommended of 1000 ppm. A 15-min break was long enough to natural change the air (reduce the CO2 concentration <1000 ppm). The threshold limit values of PM10 were met in the classroom.